Rare and protected aquatic and coastal aquatic species in the Kharkiv region (Ukraine) - Rokityansky, A.; Gamulya, Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The article presents the results of research of rare and protected aquatic and coastal aquatic species of the Kharkiv region. Using the results of field research, analysis of literature data and material of herbarium CWU it has been established that higher aquatic flora of the region includes 53 species of higher vascular plants, 120 species are related to coastal aquatic plants. А list of rare species of higher aquatic and coastal aquatic flora of the studied area has been made. The conservation status of each species has been defined. Of them four species of aquatic plants (Salvinia natans (L.) All., Trapa natans L., Utricularia intermedia Hayne, U. minor L.) and one species of coastal aquatic plants (Caldesia parnassifolia (L). Parl.) are included in the Red Book of Ukraine. One species is endemic, three species are tertiary relics. Ceratophyllum tanaiticum Sapjeg. is included in the European Red List. Two species are included in the Bern Convention List. The list of plants to be protected in the Kharkiv region (2001) includes 15 species of aquatic and 6 species of coastal aquatic plants. In general, in the Kharkiv region 18 species of aquatic plants and 13 species of aquatic coastal vascular plants are subject to protection. Another 28 species require research to establish their sozological status and necessary protection measures at the regional level.